Ambient Ammonia Synthesis via Electrochemical Reduction of Nitrate Enabled by NiCo2O4 Nanowire Array. Issue 13 (10th February 2022) - Liu, Qian; Xie, Lisi; Liang, Jie; Ren, Yuchun; Wang, Yuanyuan; Zhang, Longcheng; Yue, Luchao; Li, Tingshuai; Luo, Yongsong; Li, Na; Tang, Bo; Liu, Yang; et al.
Abstract: NiCo2 O4 nanowire array on carbon cloth (NiCo2 O4 /CC) is proposed as a highly active electrocatalyst for ambient nitrate (NO3 − ) reduction to ammonia (NH3 ). In 0.1 m NaOH solution with 0.1 m NaNO3, such NiCo2 O4 /CC achieves a high Faradic efficiency of 99.0% and a large NH3 yield up to 973.2 µmol h −1  cm −2 . The superior catalytic activity of NiCo2 O4 comes from its half‐metal feature and optimized adsorption energy due to the existence of Ni in the crystal structure. A Zn‐NO3 − battery with NiCo2 O4 /CC cathode also shows a record‐high battery performance. Abstract : NiCo2 O4 nanowire array on carbon cloth is an efficient electrocatalyst for NO3 − to NH3 conversion under ambient conditions, achieving a high Faradic efficiency of 99.0% and a large NH3 yield up to 973.2 µmol h −1  cm −2 in 0.1 m NaOH with 0.1 m NO3 − . The catalytic mechanism is investigated by theoretical calculations.